The British Museum's Excavations at Nineveh, 1846-1855 - Turner, Geoffrey, (Culture and History of the Ancient Near East ;, 2021)
Geoffrey Turner has written the definitive study of the mid-19th century excavations sponsored by the British Museum at the ancient Assyrian site of Nineveh in Iraq. Based on exhaustive analysis of unpublished archives combined with his own extensive knowledge of Assyrian architecture, Turner's work documents the complete history of these excavations. Turner also draws on the archives and numerous additional sources to provide a detailed reconstruction of the architecture and relief sculpture in the building that was the primary focus of these excavations, the Southwest Palace of Sennacherib (ruled 705-681 BC). The result constitutes the final report both on the results of these excavations and on the original appearance of one of the ancient world's most famous buildings.